The presence of psychological trauma symptoms in resuscitation providers and an exploration of debriefing practices. (September 2019) - Spencer, Stephen A.; Nolan, Jerry P.; Osborn, Mike; Georgiou, Andy
Abstract: Introduction: Witnessing traumatic experiences can cause post-traumatic stress disorder (PTSD). The true impact on healthcare staff of attending in-hospital cardiac arrests (IHCAs) has not been studied. This cross-sectional study examined cardiac arrest debriefing practices and the burden of attending IHCAs on nursing and medical staff. Methods: A 33-item questionnaire-survey was sent to 517 doctors (of all grades), nurses and health-care assistants (HCAs) working in the emergency department, the acute medical unit and the intensive care unit of a district general hospital between April and August 2018. There were three sections: demographics; cardiac arrest and debriefing practices; trauma-screening questionnaire (TSQ). Results: The response rate was 414/517 (80.1%); 312/414 (75.4%) were involved with IHCAs. Out of 1463 arrests, 258 (17.6%) were debriefed. Twenty-nine of 302 (9.6%) staff screened positively for PTSD. Healthcare assistants and Foundation Year 1 doctors had higher TSQ scores than nurses or more senior doctors (p = 0.02, p = 0.02, respectively). Debriefing was not associated with PTSD risk (p = 0.98). Only 8/67 (11.9%) of resuscitation leaders had prior debriefing training. Conclusions: Nearly 10% of acute care staff screened positively for PTSD as a result of attending an IHCA, with junior staff being most at risk of developing trauma symptoms. Very few debriefs occurred, possibly because of a lack of debrief training amongst cardiac arrest team leaders. More support is required for acute care nursing and medical staff following an IHCA.